A Titanium(IV)‐Based Metal–Organic Framework Featuring Defect‐Rich Ti‐O Sheets as an Oxidative Desulfurization Catalyst - Smolders, Simon; Willhammar, Tom; Krajnc, Andraž; Sentosun, Kadir; Wharmby, Michael T.; Lomachenko, Kirill A.; Bals, Sara; Mali, Gregor; Roeffaers, Maarten B. J.; De Vos, Dirk E.; Bueken, Bart (Angewandte Chemie International Edition, 2019)
While titanium‐based metal–organic frameworks (MOFs) have been widely studied for their (photo)catalytic potential, only a few TiIV MOFs have been reported owing to the high reactivity of the employed titanium precursors. The synthesis of COK‐47 is now presented, the first Ti carboxylate MOF based on sheets of TiIVO6 octahedra, which can be synthesized with a range of different linkers. COK‐47 can be synthesized as an inherently defective nanoparticulate material, rendering it a highly efficient catalyst for the oxidation of thiophenes. Its structure was determined by continuous rotation electron diffraction and studied in depth by X‐ray total scattering, EXAFS, and solid‐state NMR. Furthermore, its photoactivity was investigated by electron paramagnetic resonance and demonstrated by catalytic photodegradation of rhodamine 6G. COK‐47, the first Ti carboxylate sheet‐based MOF, can be synthesized as pristine or inherently defective nanoparticulate material. Its structure was extensively characterized and its defects render it a highly efficient catalyst for the oxidation of thiophenes. The material also features photocatalytic activity.